2019
DOI: 10.1108/whatt-08-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Tourism planning: impacts as benchmarks for sustainable development plans

Abstract: Purpose The purpose of this paper is to provide a comprehensive list of indicators to be used in the tourism sector, in support of the development of sustainable strategic plans. Specific objectives include making a comprehensive assessment and categorization of those indicators and facilitating an easier to use system that guarantees the use of those benchmarks as a base for objectives definition and performance standards monitorization. Design/methodology/approach This research adopted a descriptive design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To realize the Implementation of Virtual Reality Tourism requires the involvement of all components on an ongoing basis through training and mentoring. As stated by Johnston and Tyrrell (2007), Salazar and Cardoso (2019) stated the importance of providing training and development to understand sustainable tourism, which anticipates the dynamics of economic conditions, tourist behavior, and the environment. , it is necessary to establish comprehensive indicators, such as economic, socio-cultural, psychological, political, organizational factors, tourism commercialization, physical environment, and community psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…To realize the Implementation of Virtual Reality Tourism requires the involvement of all components on an ongoing basis through training and mentoring. As stated by Johnston and Tyrrell (2007), Salazar and Cardoso (2019) stated the importance of providing training and development to understand sustainable tourism, which anticipates the dynamics of economic conditions, tourist behavior, and the environment. , it is necessary to establish comprehensive indicators, such as economic, socio-cultural, psychological, political, organizational factors, tourism commercialization, physical environment, and community psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Tourists look to explore destinations in a novel way in which they can absorb local culture and immerse themselves in their visits. A study found that when social needs are derived from human behaviors, tourism practices will receive increasing attention (Salazar and Cardoso, 2019 ). Having that in mind, in order to fulfill these social needs, tourists are willing to travel, not only to explore new or distant inexperienced destinations, but also looking for authentic experience with local people and communities (Sin and Minca, 2014 ).…”
Section: Introductionmentioning
confidence: 99%